First report of fatal tick pyaemia caused by heavy infestation with the red sheep tick, Haemaphysalis punctata and co‐infection with Babesia and Theileria species. Issue 4 (1st November 2020) - Macrelli, Michele; Phipps, Paul; McGinley, Liz; Medlock, Jolyon; Johnson, Nicholas
Abstract : Tick pyaemia is a disease of sheep characterised by the development of internal abscesses caused by Staphylococcus aureus . The disease is normally triggered by infestation with Ixodes ricinus and can be exacerbated by co‐infection with Anaplasma phagocytophilum . Here the authors report the finding of tick pyaemia in a sheep flock suffering from high mortality caused by severe infestation with the red sheep tick, Haemaphysalis punctata . Tick pyaemia was confirmed by gross identification of internal abscesses in two lambs and isolation of S aureus from these lesions, with concurrent identification of H punctata ticks on the carcases. Additionally, Babesia motasi and Theileria luwenshuni were detected by pan‐piroplasm PCR in the blood of infested animals including the two sent for postmortem examination. Anaplasma phagocytophilum was not detected. These findings suggest that infestation with H punctata is capable of inducing tick pyaemia in lambs and that this may be exacerbated by coinfection with piroplasms.